Optimal Path planning on Multi-Robot Task Allocation for Manufacturing with Artificial Bee Colony Algorithm - Rawinun Praserttaweelap; Somyot Kiatwanidvilai (My University, 2021)
This research presents the optimal path planning for manufacturing. The new contribution is the safety path searching by using artificial bee colony algorithm in multi-robot systems. The new RC function was introduced in this paper to represent the risk of collision path. The best safety path searching is the low risk of collision path from automatic searching on RC function. This research designs the artificial bee colony algorithm for the safety path searching based on the manufacturing environment. The proposed is to find the optimal safety path with fast convergence. With the built-in error, the simulation results illustrate the effectiveness of the optimal path planning in multi-robot systems for manufacturing.
Keywords: Advanced Manufacturing and Logistics Optimization; Robotic Path Planning Algorithms; Manufacturing Process and Optimization